IMPACT OF IMPLEMENTING A SURGICAL SAFETY CHECKLIST IN HOSPITAL: LITERATURE REVIEW - Arimbi, Ezha Gadis Rekly; Dhamanti, Inge (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: The Surgical Safety Checklist is part of WHO's efforts to reduce the number of deaths worldwide. Purpose: To analyze the impact of implementing the WHO Surgical Safety Checklist in hospitals. Methods: Article search was carried out through PubMed and ScienceDirect databases using keywords ("impact") OR ("effect") AND ("implementation") AND ("surgical safety checklist") AND ("hospital") . The total number of articles found was 195, but only six articles met the inclusion criteria. Results: A comprehensive study in 7 hospitals located in 4 countries found the impact of implementing the Surgical Safety Checklist in hospitals could improve the quality of care, reduce the length of hospitalization, reduce mortality and complications that cause morbidity, reduce treatment costs, improve surgical team communication, increase trust in the safety culture in the operating room, improve teamwork climate, safety climate, surgical outcomes, and improve patient safety. Conclusion: Surgical Safety Checklist can reduce mortality and morbidity, improve quality of care, reduce treatment costs, and affect the attitudes & perceptions of team members and patient safety.